Students' Understanding of Plagiarism in Academic Writing: Indonesian Context - Nuur Insan Tangkelangi; Suardi Suardi; Rahmawati Upa' (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
Extensive studies identify plagiarism as a grave problem in Indonesian university students’ academic writing (Adiningrum, 2015; Sulaiman, 2015; Zalnur, 2012).Plagiarism is the most severe problem found in students’ theses in the context investigated in this study (Tangkelangi & Widyasari, 2015).However, no study explicitly examines the extent that students understand plagiarism, including both its concept and its practices in the focused context. Therefore, this study aims to fill this gap by investigating students’ understanding of plagiarism. Considering the results of previous studies related to the potential factors involved in students’ understanding of plagiarism, this study also aims to determine whether gender and academic achievement are considerable factors in students’ plagiarism understanding in the focused context. To investigate these issues, survey research using an adapted questionnaire was conducted to gather data from seventy participants out of a total population of eighty-five students, who voluntarily participated in this study. The participants were third-year students majoring in English Education who will take a unit discussing plagiarism issues in the next semester. The data gathered from the participants was analysed using the Rasch model to determine the students’ understanding of plagiarism. Then, a t-test of two independent samples was used to examine whether the students’ understanding differed between gender and a Pearson’s rtest was used to examine whether academic achievement correlated with their plagiarism understanding. The results of the analyses revealed that the students had a basic understanding of plagiarism and their understanding did not differ between gender or with academic achievement. These findings imply that several plagiarism principles need to be explored more, including unattributed paraphrasing, self-plagiarism and citations and referencing. It is also implied that special treatment for a particular gender or a certain academic achiever is not necessary.